Rehashing system security solutions in e-banking - Ul Islam Khan, Burhan; F. Olanrewaju, Rashidah; Anwar, Farhat (International Journal of Engineering and Technology, 2019)
Applications meant for exchanging cash, or individual data are becoming progressively common in mobile communications and on the Internet. The expansion of electronic banking services by utilizing various electronic channels provide added value to the users. As such, client authentication is required in these applications for affirming the legitimacy of the clients. The most widely recognized service of accreditations utilized today is the static passwords. Weak passwords prove to be an awful choice because it exposes online banking services to various security dangers. Different arrangements have been put forward to eradicate the clients’ need for the creation and management of passwords. In this regard, a typical method developed is the one-time password (OTP), i.e., passwords which remain valid for a single exchange or session. Sadly, the vast majority of these password arrangements doesn’t fulfil the requirement of usability and scalability and hence can be considered to be unreliable. In this paper, the usability and security facets of the present-day strategies for validation schemes centred on non-OTP and OTP structures are contemplated. At last, the loopholes, as well as the open challenges, are discussed, highlighting their prominence in the related field of study. Â Â